Failure analysis on Kriss motorcycle handle locking mechanism / Mackenzie Socret ... [et al.] - Socret, Mackenzie; Mohd Rawi, Mohd Ikram; Miskam, Mohd Ashriq (Faculty of Mechanical Engineering, 2002)
This thesis is about failure analysis of the Kriss motorcycle handle locking mechanism. In this analysis, we focus on the locking mechanism located at the front part of the motorcycle. Action that we are taken is, we put the light impact force to the lock (locking rod), which consists in ignition switch by using Tensile Testing Machine. We wish to analyze the types of failure that normally occur when the handle being push with a sudden force. The understanding of this analysis will enable us to come up with suggestions for a better design of the handle locking mechanism in motorcycle, in secure.